The Meaning of the Context of The Words Iḥsān and Ḥusnā in The Verses About Devotion to Parents in The Quran - Siti Ummi Habibah (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2023)
Abstract: The breadth and richness of the vocabulary in Arabic are one of the specialties of Arabic. The same word can have different meanings. This is also influenced by the context that surrounds it. One of them is the words iḥsān and ḥusnā in the Quran. This study aims to reveal the contextual meaning of the words iḥsān and ḥusnā in the verses of the Quran related to the command to worship parents. This research is a descriptive qualitative research. The data in the study were obtained through the listening method and note-taking technique. The analysis technique uses descriptive content analysis techniques to understand the meaning behind the words iḥsān and ḥusnā by looking at the context. The results showed that the words iḥsān and ḥusnā juxtaposed with the word الوالدين had different meaning implications when viewed from the context of the verse. In this case, the context that influences the meaning is the linguistic context and the context of the situation, namely what and how the verse was revealed.